General practitioner and nurse experiences of type 2 diabetes management and prescribing in primary care: a qualitative review following the introduction of funded SGLT2i/GLP1RA medications in Aotearoa New Zealand. - Norman K; Mustafa ST; Cassim S; Mullins H; Clark P; Keenan R; Te Karu L; Murphy R; Paul R; Kenealy T; Chepulis L (Cambridge University Press, 2024)
AIM: To explore the views of general practitioners (GPs) and nurses on type 2 diabetes (T2D) management, including the use of recently funded T2D medications in New Zealand (NZ) and their perceived barriers to providing optimal care. BACKGROUND: T2D is a significant health concern in NZ, particularly among Māori and Pacific adults. Characterised by prolonged hyperglycaemia, T2D is generally a progressive condition requiring long-term care. METHODS: Semi-structured interviews were conducted between July and December 2022 with 21 primary care clinicians (10 GPs and 11 nurses/nurse prescribers) from nine different general practice clinics across the Auckland and Waikato regions of NZ. Framework analysis was conducted to identify common themes in clinicians' perceptions and experiences with T2D management. FINDINGS: Three themes were identified: health-system factors, new medications, and solution-based approaches. Lack of clinician time, healthcare funding, staff shortages, and burn-out were identified as barriers to T2D management under health-system factors. The two newly funded medications, empagliflozin and dulaglutide, were deemed to be a positive change for T2D care in that they improved patient satisfaction and clinical outcomes, but several clinicians were hesitant to prescribe these medications. Participants suggested that additional education and specialist diabetes support would be helpful to inform optimal medication prescribing and that better use of a multi-disciplinary team (clinical and support staff) could support T2D care by reducing workload, addressing cultural gaps in healthcare delivery, and reducing burnout. An improved primary care work environment, including appropriate professional development to support prescribing of new medications and the value of collaboration with a non-regulated workforce, may be required to facilitate optimal T2D management in primary care. Future research should focus on interventions to increase support for both clinical teams and patients while adopting a culturally appropriate approach to increase patient satisfaction and improve health outcomes.
Keywords: medication; primary health care; qualitative research; type 2 diabetes; Adult; Female; Humans; Male; Middle Aged; Attitude of Health Personnel; Diabetes Mellitus, Type 2; General Practitioners; Hypoglycemic Agents; Interviews as Topic; New Zealand; Nurses; Practice Patterns, Physicians'; Primary Health Care; Qualitative Research; Sodium-Glucose Transporter 2 Inhibitors; Glucagon-Like Peptide-1 Receptor Agonists